Double perovskite material, manufacturing method of the same, and reversible proton ceramic electrochemical battery
The PBCSC material, with Cs+ doped as an A-site dopant, addresses the reduced catalyst activity in R-PCEC air electrodes, enhancing electrochemical performance and stability at medium and low temperatures.
Patent Information
- Application Number
- JP2024113691
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Priority Date
- 2023-07-21
- Filing Date
- 2024-07-16
- Publication Date
- 2025-01-31
- Estimated Expiration
- 2044-07-16
AI Technical Summary
Existing reverse proton ceramic electrochemical cells (R-PCEC) face reduced electrochemical performance and increased reaction dynamics at medium and low temperatures due to the decrease in catalyst activity of the air electrode, necessitating improved air electrode materials with high ORR/OER activity.
The development of a double perovskite material, PRBA1-xCsxCo2O6-δ (PBCSC), where Cs+ is doped as an A-site dopant to enhance the electrochemical stability and catalytic activity of the air electrode by improving oxygen ion conductivity and reducing polar impedance.
The PBCSC material exhibits enhanced electrochemical performance and stability at medium and low temperatures, with reduced polar impedance and increased catalyst activity, leading to improved energy conversion efficiency in R-PCEC batteries.
Smart Images

Figure 2025016367000001_ABST
Abstract
Description
[Technical field]
[0001] The present invention relates to the field of reversible protonic ceramic electrochemical cells, and in particular to a double perovskite material and its preparation method, and a reversible protonic ceramic electrochemical cell. [Background technology]
[0002] Due to the finiteness of fossil fuel reserves and the intensification of greenhouse gas emissions, there is a strong need to find clean and non-polluting energy conversion devices to alleviate the current energy and environmental crisis. Reversible proton ceramic electrochemical cell (R-PCEC) technology can be one of the effective means to solve the current problem. When the reversible proton ceramic electrochemical cell works in fuel cell mode, it can convert chemical energy into electrical energy, and when it works in electrolysis mode, it can convert electrical energy into chemical energy. In addition, R-PCEC based on proton conductor electrolyte has relatively high proton conductivity, so it can operate at low and medium temperatures (400-700°C). The relatively low operating temperature of R-PCEC is not only advantageous for extending the life of the battery itself, but also for reducing the manufacturing cost. However, as the operating temperature of R-PCEC decreases, the reaction kinetics of the air electrode also slows down, and the electrochemical performance of R-PCEC is significantly reduced. Therefore, designing air electrode materials that have high catalytic activity for the oxygen reduction reaction (ORR) / oxygen evolution reaction (OER) and sufficient chemical stability under low and medium temperature operating conditions is one of the most critical challenges facing R-PCEC.
[0003] In recent years, researchers have designed many air electrode materials, most of which show moderate electrochemical performance in R-PCEC. The double perovskite material PrBaCoO 6-δ(PBC) has excellent electrical conductivity, oxygen ion conductivity, oxygen surface exchange coefficient, and oxygen ion diffusion kinetics, and shows excellent electrochemical performance as the air electrode of solid oxide fuel cells (SOFC). Cesium (Cs) is often used in designing perovskite solar cell materials because the doping of Cs can enhance the thermal stability and moisture resistance of the crystal structure of the material. According to density functional theory (DFT) calculations, the main reason for the improvement of the ORR activity of the air electrode after Cs doping is the shift of electron pairs due to the polarization distribution at the A-site and B-site of Lewis acid strength, which further reduces the oxygen vacancy formation energy of the oxide. At present, there are few reports on the application of the air electrode designed by doping Cs at the A-site to R-PCEC. Summary of the Invention [Problem to be solved by the invention]
[0004] In order to solve the above problems, the present invention provides a double perovskite material, a method for producing the same, and a reversible protonic ceramic electrochemical cell. + The double perovskite material doped with the low Lewis acidity cation Cs has good electrochemical stability, relatively low polarization impedance, and relatively high ORR / OER activity. + Based on said double perovskite material, the present invention further provides a reversible protonic ceramic electrochemical cell having excellent electrochemical performance and exhibiting good stability. [Means for solving the problem]
[0005] Specifically, in a first aspect, the present invention provides a double perovskite material, the general formula of which is: PrBa 1-x Cs x Co2O 6-δ where δ is the oxygen vacancy content.
[0006] According to the present invention, when doping with an A-site dopant with a relatively low acidity, it is advantageous to improve the hydration ability of the perovskite oxide. In addition, in the air electrode of the fuel cell, Cs is applied as the A-site cation dopant, and the kinetics of the redox reaction of the air electrode is closely related to the Lewis acidity strength of the doped ion. Cs + When Cs is used as an A-site dopant, the electron pair shift caused by the polarization distribution of the Lewis acid strength of the A-site ions and B-site ions increases the oxygen vacancy content in the oxide, which is favorable for improving the oxygen exchange kinetics on the electrode surface and accelerating the redox reaction process. Therefore, Cs + The doping of Ba in the double perovskite oxide PBC can effectively improve the catalytic activity of the air electrode and the electrochemical performance of the R-PCEC at low and medium temperatures. + In addition, the present invention uses a novel double perovskite material, PrBa, as the air electrode of the R-PCEC. 1-x Cs x Co2O 6-δ (PBCsC) was designed and fabricated, and its electrocatalytic activity and water decomposition ability at low and medium temperatures were evaluated, which has important practical significance for the design and realization of air electrodes with high catalytic activity and stability and their application in R-PCEC.
[0007] Preferably, the value of x is in the range of 0.01 to 0.15.
[0008] More preferably, the value of x is in the range of 0.05 to 0.125.
[0009] Preferably, the double perovskite material has a tetragonal layered perovskite structure. The double perovskite material has a perovskite structure in which Cs is doped at the A site. In the present invention, the ionic radius of Cs is 167 pm, and the ionic radius of Ba is 135 pm, and the ionic radius of Ba is closest to that of Cs (Pr 3+ and Pr4+ The ionic radii of Co are 99 and 85 pm. 2+ , Co 3+ , Co 4+ The ionic radii of are 74.5, 61, and 53 pm, respectively, and the Ba ions in the structure are Cs + is replaced by More preferably, the lattice constants are a=3.9045±0.1 Å, b=3.9045±0.1 Å, and c=7.6572±0.1 Å.
[0010] More preferably, the general formula of the double perovskite material is PrBa 0.9 Cs 0.1 Co2O 6-δ where 0.1≦δ≦0.3.
[0011] According to the present invention, it has been further discovered through experimental research that PBCsCs using the above x values in the present invention have excellent electrocatalytic performance. In particular, when the preferred x=0.1 is used to partially replace Ba, it is unexpected that the reversible protonic ceramic electrochemical cell can have better electrochemical performance and stability than the other values.
[0012] In a second aspect, the present invention provides a method for producing the double perovskite material, comprising the steps of: (1) dissolving praseodymium nitrate, barium nitrate, cesium nitrate and cobalt nitrate in water to obtain a mixed solution, and then mixing the mixed solution with ethylenediaminetetraacetic acid, citric acid and aqueous ammonia to adjust the pH to 7 to 8 to obtain a mixed solution; and (2) A step of heating the mixed solution until it becomes gel-like, performing a high-temperature treatment at 200 to 250° C., obtaining a precursor, and then calcining the precursor. Includes.
[0013] Preferably, in step (1), the molar ratio of the metal element, ethylenediaminetetraacetic acid, and citric acid is 0.5-1.5:0.5-1.5:1-2, and preferably 1:1:1.5, where the metal element is the sum of Pr, Ba, Cs, and Co. Experimental studies have shown that the present invention can produce PrBa by using a specific ratio of the metal element, ethylenediaminetetraacetic acid, and citric acid in combination with the preferred firing temperature of the present invention. 0.9 Cs 0.1 Co2O 6-δ The phase formation effect (crystal strength) of PrBa can be significantly improved. 0.9 Cs 0.1 Co2O 6-δ It has been found that the crystalline structure of the crystalline silicon can be improved.
[0014] Preferably, in step (2), the mixed solution is heated to a temperature of 80 to 100°C.
[0015] Preferably, in step (2), the high-temperature treatment is carried out for a period of 2 to 6 hours, preferably 2 hours.
[0016] Preferably, in step (2), the firing temperature is 950 to 1050° C., and is preferably 1000° C., and the firing time is 2 to 4 hours, and is preferably 2 hours.
[0017] In the present invention, by combining the raw materials used with the preferred manufacturing conditions, the phase formation effect can be made more favorable, and PrBa2O3 having superior crystal strength and crystal structure can be obtained. 0.9 Cs 0.1 Co2O 6-δ Moreover, the reversible protonic ceramic electrochemical cell produced thereby can have better overall performance in terms of electrochemical performance and stability.
[0018] In a third aspect, the present invention provides the use of the double perovskite material as an air electrode in a reversible protonic ceramic electrochemical cell.
[0019] In a fourth aspect, the present invention further provides an anode-supported reversible protonic ceramic electrochemical cell, comprising an anode support layer, an electrolyte and an air electrode, connected in series, the air electrode being formed from a cation of low Lewis acid strength, Cs, as described above. + The material was fabricated from a double perovskite material (doped with ZnO).
[0020] Preferably, the electrolyte material is BaZr 0.1 Ce 0.7 Y 0.1 Yb 0.1 O 3-δ (BZCYYb1711), where δ is the oxygen vacancy content (0≦δ≦0.2).
[0021] Preferably, the material of the anode support layer is NiO and BaZr 0.1 Ce 0.7 Y 0.1 Yb 0.1 O 3-δ where NiO and BaZr 0.1 Ce 0.7 Y 0.1 Yb 0.1 O 3-δ The mass ratio of these is 5.5-6.5:3.5-4.5, preferably 6:4, and δ is the oxygen vacancy content.
[0022] Preferably, the reversible protonic ceramic electrochemical cell further comprises a transition layer, the transition layer being disposed between the anode support layer and the electrolyte. Preferably, the transition layer comprises NiO and BaZr 0.1 Ce 0.7 Y 0.1 Yb 0.1 O 3-δ (BZCYYb1711), where NiO and BaZr 0.1 Ce 0.7 Y0.1 Yb 0.1 O 3-δ The mass ratio of these is 5.5-6.5:3.5-4.5, preferably 6:4, and δ is the oxygen vacancy content.
[0023] According to the present invention, the term δ in each layer of the reversible protonic ceramic electrochemical cell means the oxygen vacancy content, which means that unless the range is limited in the present invention, the range of the oxygen vacancy content may be any range commonly used in the art, such as 0-0.5, 0.1-0.4, or 0.1-0.2.
[0024] In the present invention, the anode-supported protonic ceramic electrochemical cell uses a co-casting method, in which the electrolyte layer, transition layer, and anode layer are closely connected without interlayer separation, which significantly improves the stability of the half-cell structure and improves and reduces the resistance due to the connection of the half-cell, so that the anode-supported protonic ceramic electrochemical cell can exhibit better electrochemical performance.
[0025] More preferably, the method for producing the anode supported reversible protonic ceramic electrochemical cell comprises the steps of: (1) preparing a slurry of an anode support layer material, a transition layer material, an electrolyte material, and an air electrode material; (2) casting the electrolyte slurry, the transition layer slurry, and the anode supporting layer slurry in this order in a casting apparatus, and then air-drying the co-cast sheets after air-drying for 10 to 14 hours; degreasing the co-cast sheets and firing them at a high temperature to obtain an anode-supported half cell (preferably, the heat treatment and degreasing conditions are 500 to 700° C. for 1 to 3 hours, and the high-temperature firing conditions are 1400 to 1500° C. for 4 to 6 hours); and (3) forming a slurry of the material of the air electrode, applying it to the surface of the electrolyte of the half-cell, and firing it at a high temperature to obtain an anode-supported reversible protonic ceramic electrochemical full cell (preferably, the high-temperature firing conditions are 800 to 1000° C. for 1 to 3 hours); Includes.
[0026] More preferably, the substrate is a polymer film.
[0027] More preferably, the electrolyte layer slurry is obtained by ball milling BZCYYb1711 powder, a dispersant and absolute ethanol.
[0028] More preferably, the transition layer slurry is obtained by blending BZCYYb1711 powder, nano nickel oxide, graphite, dispersant, anhydrous ethanol and butyl acetate and ball milling for 12 hours.
[0029] More preferably, the anode supporting layer slurry is obtained by blending BZCYYb1711, nickel oxide, graphite, a dispersant, absolute ethanol, and butyl acetate, and pulverizing the mixture in a ball mill for 10 to 14 hours.
[0030] More preferably, the air electrode slurry comprises PrBa 0.9 Cs 0.1 Co2O 6-δ The material is blended with terpineol, and the slurry composition is 1g:0.5-0.7g PrBa 0.9 Cs 0.1 Co2O 6-δ and terpineol.
[0031] More preferably, in said anode supported half-cell, the electrolyte layer has a thickness of 7-9 μm, the anode support layer has a thickness of 600-700 μm, and the transition layer has a thickness of 16-22 μm.
[0032] In the present invention, it has been found through testing and research that when the above-mentioned preferred high-temperature sintering temperature and time parameters are employed to manufacture an anode-supported half-cell, the thickness of the anode support layer can be adjusted to improve the mechanical strength of the half-cell, and the anode-supported half-cell exhibits better structural stability. Effect of the Invention
[0033] The beneficial effects of the present invention are at least as follows: + The doped double perovskite material is the double perovskite material PrBaCoO 6-δ Based on this, the A-site was doped with elements. The sol-gel method was used to fabricate the air electrode material PrBa for anode-supported reversible protonic ceramic electrochemical cells. 0.9 Cs 0.1 Co2O 6-δ The air electrode material of the anode-supported reversible protonic ceramic electrochemical cell of the present invention has a relatively low polarization impedance and a relatively high electrocatalytic activity. The anode-supported single cell prepared in the present invention, i.e., NiO-BZCYYb1711||transition layer NiO-BZCYYb1711||BZCYYb1711||PBCsC, has a polarization resistance of 0.045 Ω cm at 650°C, 600°C, 550°C and 500°C, respectively. 2 , 0.094Ωcm 2 , 0.273Ωcm 2 and 1.037 Ω cm 2 and the maximum power density is 1.66Wcm -2 , 1.19Wcm -2 , 0.72Wcm -2 and 0.41Wcm -2 When the R-PCEC was operated in electrolysis mode after supplying humidified air to the air electrode side, the current density at 1.3 V was −2.85 A cm at 650 °C, 600 °C, 550 °C, and 500 °C, respectively. -2 , -1.48Acm -2 , -0.71Acm -2 , and -0.31Acm -2 The anode-supported reversible protonic ceramic electrochemical cell of the present invention has excellent stability, oxygen ion exchange kinetics, electrocatalytic activity and electrochemical performance.
[0034] In order to more clearly describe the technical solutions in the embodiments of the present invention and the prior art, the following briefly describes the drawings that need to be used in the description of the embodiments or the prior art. The drawings in the following description are some embodiments of the present invention, and it is obvious to those skilled in the art that they can obtain other drawings based on these drawings without creative labor. [Brief description of the drawings]
[0035] [Figure 1] 1 is a refined XRD pattern of the air electrode material PrBa0.9Cs0.1Co2O6-δ (PBCsC) according to Example 1 of the present invention after calcination at 1000°C for 2 hours. [Diagram 2] 1 shows the XRD patterns of the air electrode material PrBa0.9Cs0.1Co2O6-δ (PBCsC) and the electrolyte BZCYYb powder according to Example 1 of the present invention after co-firing at 950°C for 2 hours in a high-temperature muffle furnace. [Diagram 3] 1 shows an XRD pattern of the air electrode material PrBa0.9Cs0.1Co2O6-δ (PBCsC) according to Example 1 of the present invention after treatment with 30% water at 600°C for 10 hours. [Figure 4] 1 is a high-temperature in situ XRD pattern of the air electrode material PrBa0.9Cs0.1Co2O6-δ (PBCsC) according to Example 1 of the present invention after calcination at 1000°C for 2 hours. [Diagram 5] 1 shows X-ray photoelectron spectra (XPS) of air electrode materials PBCsC and PBC according to Example 1 of the present invention, where a is Pr 3d and b is Co 2p. [Figure 6] 6 shows O 1s X-ray photoelectron spectra of air electrode materials PBCsC (6a) and PBC (6b) according to Example 1 of the present invention. [Figure 7] FIG. 2 is a diagram showing an evaluation of the relaxation properties of air electrode materials PBCsC and PBC according to Example 1 of the present invention. [Figure 8]FIG. 8a shows the area specific impedance (8b) and impedance stability (8c) in humid air (3% HO) of a symmetric cell (PBCsC as electrode and BZCYYb1711 as electrolyte support) according to Example 1 of the present invention. [Figure 9] FIG. 2 is a diagram showing the electrochemical stability in humid air (3% H2O) of a symmetric cell according to Example 1 of the present invention (wherein PBCsC and PBC are electrodes and BZCYYb1711 is the electrolyte support). [Figure 10] 1 shows infrared spectra of PBCsC and PBC oxide according to Example 1 of the present invention after treatment at 600° C. for 50 hours in air containing 30% water vapor. [Figure 11] FIG. 13 is a graph showing the maximum power density measured in FC mode (humidified hydrogen gas is supplied to the anode side and air is supplied to the oxygen electrode side) in the range of 650 to 500°C for a single cell (Ni-BZCYYb1711|| transition layer Ni-BZCYYb1711|| BZCYYb1711|| PBCsC) manufactured using Ni-BZCYYb1711 as the fuel electrode support in Example 2 of the present invention when PBCsC is used as the air electrode. [Figure 12] This figure shows the current density corresponding to 1.3 V when a single cell (Ni-BZCYYb1711|| transition layer Ni-BZCYYb1711|| BZCYYb1711|| PBCsC) manufactured using Ni-BZCYYb1711 as the fuel electrode support in Example 2 of the present invention is used as the air electrode. The cell is measured in EC mode (humidified hydrogen gas is supplied to the anode side and humidified air is supplied to the oxygen electrode side) in the range of 650 to 500 °C. [Figure 13] FIG. 13 is a diagram showing the operational stability of a single cell (Ni-BZCYYb1711||transition layer Ni-BZCYYb1711||BZCYYb1711||PBCsC) manufactured using PBCsC according to Example 2 of the present invention as an air electrode and Ni-BZCYYb1711 as an anode support, measured at 650° C. in a fuel cell mode and an electrolyzer mode. [Figure 14]FIG. 13 is a diagram showing the cycle stability of a single cell (Ni-BZCYYb1711||transition layer Ni-BZCYYb1711||BZCYYb1711||PBCsC) manufactured using PBCsC according to Example 2 of the present invention as an air electrode and Ni-BZCYYb1711 as an anode support, when the cell was measured at 600° C. [Figure 15] FIG. 13 is a graph showing the change in the faradaic efficiency of a single cell according to Example 2 of the present invention, which is manufactured using PBCsC as an air electrode and Ni-BZCYYb1711 as an anode support layer (Ni-BZCYYb1711||transition layer Ni-BZCYYb1711||BZCYYb1711||PBCsC). [Figure 16] FIG. 13 is a graph showing the change in hydrogen evolution rate with the applied current density of a single cell (Ni-BZCYYb1711|| transition Ni-BZCYYb1711||BZCYYb1711||PBCsC) manufactured using PBCsC according to Example 2 of the present invention as an air electrode and Ni-BZCYYb1711 as an anode supporting layer. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0036] In order to make the objectives, technical solutions and advantages of the embodiments of the invention clearer, the following clearly and completely describes the technical solutions in the embodiments of the present invention. It is obvious that the described embodiments are only some of the embodiments of the present invention, and not all of the embodiments. Based on the embodiments of the present invention, all other embodiments that can be obtained by those skilled in the art without creative labor are all within the protection scope of the present invention.
[0037] Unless otherwise specified, all raw materials and reagents used in the following examples are commercially available or can be prepared by known methods. In the examples, if no specific techniques or conditions are specified, they are performed according to conventional methods or techniques or conditions described in the literature in the field, or according to the product instructions. If the manufacturer of the reagent or device used is not specified, they are all ordinary products that can be purchased through official channels.
[0038] The present invention will be described in more detail below with reference to examples.
[0039] An embodiment of the present invention is a cation having a low Lewis acid strength, Cs + The air electrode material is doped with PrBa 0.9 Cs 0.1 Co2O 6-δ (PBCsC). The perovskite material PrBaCoO 6-δ The doping of Cs ions into the A site of the anode-supported reversible protonic ceramic electrochemical cell improves the oxygen reduction / evolution reaction activity and stability. + Doping at the A site of PrBa 0.9 Cs 0.1 Co2O 6-δ (PBCsC) The catalytic activity and stability of the air electrode are both improved. At 650 °C, the single cell with the composition Ni-BZCYYb1711|transition layer Ni-BZCYYb1711|BZCYYb1711|PBCsC has a maximum output power of 1.66 W cm in FC mode. -2 and the polarization resistance of the battery is only 0.045 Ω cm 2 After supplying air containing 3% water vapor to the air electrode side, the current was -2.85 Acm at 650°C and 1.3 V. -2 The present invention uses the cation Cs with low Lewis acid strength. + By doping with PrBaCoO 6-δ The polarization impedance of the air electrode can be significantly reduced, and the electrochemical performance of the whole cell can be improved. In the electrolysis mode, the current density can be significantly improved and excellent stability can be exhibited.
[0040] At present, there are relatively few studies on the cycle stability of low-temperature anode-supported reversible protonic ceramic electrochemical cells, and the stability characterization methods of reversible protonic ceramic electrochemical cells are also very scarce. In order to characterize the cycle stability of the reversible protonic ceramic electrochemical cell of the present invention, the embodiment of the present invention further provides a characterization method. The main steps are: coating the air electrode material on the electrolyte membrane of the anode-supported proton conductor single cell, supplying hydrogen gas containing 3% water vapor to the anode side, and supplying air containing 3% water vapor to the air electrode side. The single cell is subjected to cycle stability measurement, i.e., ±0.5Acm -2 The anode-supported reversible protonic ceramic electrochemical cell is alternately and repeatedly operated in fuel cell and electrolyzer modes, respectively, by applying a current of 0.1 V to the air electrode, and the electrochemical stability of the air electrode is evaluated.
[0041] In the following examples, PBC is used as a comparative sample, and its components are PrBaCoO 6-δ The manufacturing process is the same as that of the embodiment.
[0042] Example 1 In this example, PrBa is an air electrode material for an anode-supported reversible protonic ceramic electrochemical cell. 0.9 Cs 0.1 Co2O 6-δ The specific steps are as follows:
[0043] (1) Stoichiometric ratios of praseodymium nitrate, barium nitrate, cesium nitrate and cobalt nitrate are PrBa 0.9 Cs 0.1 Co2O 6-δ The metal ions were added to the deionized water solution in the chemical ratio of (PBCsC). Then, citric acid was added in an amount 1.5 times the number of moles of the metal ions, and ethylenediaminetetraacetic acid was added in an amount 1 time the number of moles of the metal ions. Here, praseodymium nitrate, barium nitrate, cesium nitrate, cobalt nitrate, citric acid, and ethylenediaminetetraacetic acid were obtained from the Aladdin Chemical Reagents website.
[0044] (2) After adding a complexing agent to the solution in which the metal ions were dissolved, ammonia water was added and the pH value was adjusted to 7 to 8. The solution was then heated and stirred under magnetic stirring conditions until the water evaporated to dryness, obtaining a gel-like substance.
[0045] (3) The gel-like material was placed in a fan oven and dried at 250°C for 2 hours to obtain a bulky, porous precursor.
[0046] (4) The precursor is placed in a high-temperature muffle furnace and calcined at 1000 °C for 2 hours to obtain the desired air electrode material powder, PrBa 0.9 Cs 0.1 Co2O 6-δ (hereinafter referred to as PBCsC), where 0.1≦δ≦0.3.
[0047] Example 2 In this example, PrBa provided in Example 1 0.9 Cs 0.1 Co2O 6-δ A reversible protonic ceramic electrochemical cell supported by an anode of Ni-BZCYYb1711|transition layer Ni-BZCYYb1711|BZCYYb1711|PBCsC is provided, in which (PBCsC) is used as the air electrode of the cell, and specifically includes the following steps:
[0048] (1) Preparation of electrolyte layer slurry: 3g of BZCYYb1711 powder, 0.1g of fish oil dispersant, 0.8g of anhydrous ethanol, and 0.8g of butyl acetate were mixed uniformly to obtain BZCYYb1711 electrolyte layer slurry. Preparation of transition layer slurry: 1.2g of BZCYYb1711 powder, 1.8g of nano nickel oxide, 0.3g of graphite, 0.1g of fish oil dispersant, 0.75g of anhydrous ethanol, and 0.75g of butyl acetate were mixed uniformly to obtain Ni-BZCYYb1711 transition layer slurry. Preparation of anode support layer slurry: 10g of BZCYYb1711, 15g of nickel oxide, 1.5g of graphite, 1g of fish oil dispersant, 3g of anhydrous ethanol, and 3g of butyl acetate were mixed uniformly to obtain anode slurry. The above slurries were each charged into a drum rotary ball mill and pulverized in the ball mill for 30 to 40 hours.
[0049] (2) The electrolyte slurry, transition layer slurry and anode slurry blended by ball milling were successively cast onto a polymer film, which was a PET (polyethylene terephthalate) release film, and the co-cast electrolyte layer-transition layer-anode support layer film was naturally dried in air for 12 hours, and then cut into several 15 mm diameter sheets using a 15 mm diameter mold, which were placed in a muffle furnace and degreased at 600 ° C for 2 hours. Finally, the degreased sheets were placed in a high-temperature muffle furnace and sintered at 1450 ° C for 5 hours to obtain the desired anode-supported half-cell. Here, the anode-supported half-cell produced included a BZCYYb1711 electrolyte layer (7-9 μm thick), a Ni-BZCYYb1711 transition layer (30 μm thick) and a Ni-BZCYYb1711 anode support layer (600-700 μm thick).
[0050] (3) 1 g of the air electrode powder PrBa produced in Example 1 0.9 Cs 0.1 Co2O 6-δ 0.6 g of terpineol was weighed and mixed uniformly to obtain the desired air electrode slurry.
[0051] (4) The prepared air electrode slurry was coated on the electrolyte membrane of the half-cell, and then placed in an oven at 70°C. After the cathode slurry was dried, the assembled whole cell was sintered in a high-temperature muffle furnace at 950°C for 2 hours and used to measure the electrochemical performance in FC and EC modes.
[0052] Characterization results 1. Characterization by XRD Figure 1 shows PrBa 0.9 Cs 0.1 Co2O 6-δThe refined XRD pattern of (PBCsC) powder after calcination at 1000℃ for 2 hours shows that the synthesized PBCsC shows a single double perovskite phase structure. At the same time, the XRD refinement results show that the synthesized PBCsC has a tetragonal layered perovskite structure with lattice parameters a=b=3.9045Å, c=7.6572Å (refinement parameter: GOF=2.13).
[0053] Figure 2 shows the chemical compatibility between the synthesized air electrode material PBCsC and the electrolyte BZCYYb1711 powder. As can be seen from the figure, after mixing PBCsC and BZCYYb1711, no chemical reaction occurs even after baking at 950℃ in a high-temperature muffle furnace for 2 hours, which indicates that the PBCsC material and BZCYYb1711 powder have good chemical compatibility.
[0054] Figure 3 shows PrBa 0.9 Cs 0.1 Co2O 6-δ This is an XRD pattern after treating the (PBCsC) powder in air containing 30% water vapor at 600°C for 10 hours. Here, the main peak in the XRD pattern of the treated PBCsC clearly shifts to the lower angle side, which is thought to be due to the expansion of the lattice due to the penetration of water vapor into the lattice.
[0055] Figure 4 shows PrBa 0.9 Cs 0.1 Co2O 6-δ This is a high-temperature in situ XRD pattern of (PBCsC) powder. As can be seen from the figure, in the measurement in which the PBCsC powder was continuously heated from 100 to 700°C (the heating time at each temperature was 1 hour), no impurity phase was generated, which indicates that the PBCsC oxide exhibits good phase structure stability and chemical stability at high temperatures. In the high-temperature in situ XRD measurement of the PBCsC oxide, as the measurement temperature increases, the main peak of PBCsC shifts to the lower angle side, which is thought to be due to the expansion of the lattice with increasing temperature.
[0056] 2. Characterization by X-ray photoelectron spectroscopy (XPS) According to the fitting data, after a part of the Ba element in the A site in PBC is replaced by Cs, the proportion of the high valence states of Pr (Fig. 5(a)) and Co (Fig. 5(b)) further increases in the material to maintain its electroneutrality. As shown in Fig. 5(a), the Pr in PBC 4+ The content of Pr in PBCsC was 37.9%. 4+ The content of Co increased to 41.1%. As shown in Fig. 5(b), the Co element showed a similar trend. 3+ and Co 4+ The contents of Pr and Co were 36.7% and 35.0%, respectively, while in PBCsC, their contents increased to 41.8% and 43.5%, respectively. The XPS results show that the contents of high valence cations of Pr and Co increased by doping PBC with Cs. The corresponding O 1s XPS fitting data of PBC and PBCsC are shown in Figure 6(a, b). Here, the O 1s of PBC and PBCsC can be divided into four subordinate peaks. The subordinate peaks at binding energies of 528.3, 530.0, 531.4, and 533.4 eV are lattice oxygen (O lat ), high oxygen (O - / O2 2- ), adsorbed oxygen (O ads ) and oxygen in a hydroxyl environment (OH - ), where O - / O2 2 and O lat The ratio of PBC to PBCsC reflects the content of oxygen vacancies, and the ratios are 1.49 and 2.03, respectively. - / O2 2- The proportion of is usually believed to play an important role in the ORR process.
[0057] 3. Mitigation characteristics evaluation Fig. 7 shows the surface exchange coefficient k of PBCsC and PBC at measurement temperatures of 550 to 650 °C. * chemand the bulk diffusion coefficient D * chem Here, according to calculations, the surface exchange coefficient of PBCsC at the measurement temperature of 650°C is 7.98 × 10 -4 cms -1 and the surface exchange coefficient of PBC measured under the same conditions (2.31 × 10 -4 cms -1 ) was higher. * chem The increase in value indicates that the PBCsC air electrode has relatively fast oxygen surface exchange kinetics, which accelerates the ORR reaction. * chem The results of the same trend are also shown. * chem The values are 2.64×10 -5 and 9.01 × 10 -5 cm 2 s -1 It was. PBCsC's D * chem A higher value means that PBCsC has better oxygen diffusion kinetics. Therefore, the increase in electrocatalytic activity of the PBCsC air electrode is attributed to the doping of the A-site dopant (Cs) which generates more oxygen vacancies and improves the surface exchange kinetics.
[0058] 4. Electrochemical impedance and stability studies First, the electrocatalytic activity of the PBCsC air electrode was investigated by measuring the area-specific resistivity in humid air (3% HO) at 700–500 °C for the BZCYYb1711-supported symmetric cell. As shown in Fig. 8(a), the area-specific resistivity values of the PBCsC air electrode were 0.067, 0.184, 0.276, 0.575, and 1.588 Ω cm at 700, 650, 600, 550, and 500 °C, respectively. 2 Figure 8(b) shows the electrocatalytic activity of the PBC air electrode. Under the same measurement conditions, the area-specific resistivity of the PBC air electrode was 0.113, 0.258, 0.372, 0.977, and 2.443 Ω cm at 700, 650, 600, 550, and 500 °C, respectively.2 Compared with the PBC air electrode, the PBCsC air electrode has a relatively high electrocatalytic activity.
[0059] Figure 9 shows the stability of PBCsC and PBC in humid air (3% H2O). When exposed to humid air, the area specific resistance of the PBC air electrode increased significantly with the extension of the measurement time. Meanwhile, under the same measurement conditions, the area specific resistance of the PBCsC air electrode showed better stability. Based on the above analysis, the symmetric cell with the PBCsC air electrode has good stability and relatively high electrocatalytic activity.
[0060] 7. Characterization by Fourier transform infrared spectroscopy (FTIR) Figure 10 shows the Fourier transform infrared spectra of PBCsC and PBC air electrodes after treatment with humid air containing 30% water vapor at 600 °C for 50 h. The FTIR measurement can identify the signal value of the hydroxyl group in the oxide, and its characteristic peak is at 3400–3800 cm. -1 The measurement results show that the hydroxyl peak intensity of 30% steam-treated PBCsC is slightly higher than that of PBC oxide, indicating that PBCsC exhibits better hydration behavior.
[0061] 8. Electrochemical performance measurement Using the cell produced in Example 2, the electrochemical power density was measured in fuel cell mode (FC mode), and the current density was measured in electrolysis mode (EC mode). Figure 11 shows the results of measurements of a full cell using PBCsC of the present invention as the air electrode in fuel cell mode, with humidified hydrogen gas supplied to the anode side and air as the atmosphere on the air electrode side. The power density measured within the range of 650 to 500°C was 1.66 Wcm. -2 , 1.19Wcm -2 , 0.72Wcm -2 , and 0.41Wcm -2 It was.
[0062] 12 shows an IV curve of a single cell (Ni-BZCYYb1711||BZCYYb1711||PBCsC) manufactured using PBCsC of the present invention as the air electrode and Ni-BZCYYb1711 as the fuel electrode support, measured in EC mode (humidified hydrogen gas is supplied to the anode side and humidified air is supplied to the oxygen electrode side) in the range of 650 to 500°C. Here, the electrolytic cell with the PBCsC air electrode also showed superior electrolysis performance, and the current density at a voltage condition of 1.3 V was −2.85 A cm at 650, 600, 550 and 500°C, respectively. -2 , -1.48Acm -2 , -0.71Acm -2 , and -0.31Acm -2 It was.
[0063] 9. Stability and cycle test of single cell Figure 13 shows the current density of the PBCsC air electrode at 650°C and 0.5 A cm -2 The long-term stability of the cells is shown when operated in FC mode for 170 hours at a current density of -0.5 A cm. Also, because moist air is present in the R-PCEC air electrode chamber, the resistance of the air electrode to steam is very important for the stability of the cells. All cells with PBCsC as the air electrode show good stability in electrolysis mode using moist air (3% HO) as the oxidant, with a current density of -0.5 A cm. -2 and 650℃ for 200 hours. -2 A cycle test was performed at temperatures of 400 and 600 °C, switching between FC and EC modes at 2-h intervals (Figure 14). The battery with PBCsC air electrode showed good stability during a reversible operation period of 80 h.
[0064] 10. Measurement of Faraday efficiency and hydrogen production rate
[0065] The faradaic efficiency is crucial for hydrogen production in the R-PCEC electrochemical process, and is defined as the ratio of the actual H2 production rate (detected by gas chromatography) to the theoretical H2 production rate (calculated from the applied current). Figures 15 and 16 show the faradaic efficiency and hydrogen production rate at different current densities and 600°C in humid air (vapor concentration 30%). As shown in Figure 15, the cell was operated at -0.5, -0.75 and -1.0 A cm -2 The faradaic efficiency decreased from 85.37% to 60.86% and 48.88% when the current densities were -0.5, -0.75 and -1.0 A cm, as shown in Figure 16. -2 When , the corresponding H2 production rates increased from 2.98 to 3.18 and 3.41.
[0066] It should be noted that the above embodiments are merely for explaining the technical solutions of the present invention, and are not intended to limit the same. Although the present invention has been described in detail with reference to the above embodiments, those skilled in the art should understand that the technical solutions described in the above embodiments may be modified or some of the technical features may be replaced with equivalents, and such modifications or replacements do not deviate from the spirit and scope of the technical solutions of the embodiments of the present invention.
Claims
1. The general formula is PrBa 1-x Cs x Co 2 O 6-δ where δ is the oxygen vacancy content A double perovskite material.
2. The value of x is in the range of 0.01 to 0.15, and preferably in the range of 0.05 to 0.
125.
2. The double perovskite material according to claim 1 ,
3. The double perovskite material has a tetragonal layered perovskite structure, and preferably has lattice constants a of 3.9045±0.1 Å, b of 3.9045±0.1 Å, and c of 7.6572±0.1 Å.
2. The double perovskite material according to claim 1 ,
4. The general formula is PrBa 0.9 Cs 0.1 Co 2 O 6-δ is 2. The double perovskite material according to claim 1 ,
5. (1) dissolving praseodymium nitrate, barium nitrate, cesium nitrate and cobalt nitrate in water to obtain a mixed solution, and then mixing the mixed solution with ethylenediaminetetraacetic acid, citric acid and aqueous ammonia to adjust the pH to 7-8 to obtain a mixed solution; and (2) heating the mixed solution until it becomes gel-like, performing high-temperature treatment at 200 to 250° C. to obtain a precursor, and calcining the precursor; A method for producing the double perovskite material according to any one of claims 1 to 4, comprising:
6. In step (1), the molar ratio of the metal element, ethylenediaminetetraacetic acid, and citric acid is 0.5-1.5:0.5-1.5:1-2, and the metal element is the sum of Pr, Ba, Cs, and Co.
6. A method for producing a double perovskite material according to claim 5.
7. In step (2), the heating temperature of the mixed solution is 80 to 100° C., and / or the high-temperature treatment time is 2 to 6 hours, and / or the baking temperature is 950 to 1050° C., and the baking time is 2 to 4 hours.
6. A method for producing a double perovskite material according to claim 5.
8. Use of double perovskite materials as air electrodes in reversible protonic ceramic electrochemical cells Use of the double perovskite material according to any one of claims 1 to 4.
9. A cathode support layer, an electrolyte and an air electrode connected in series, the air electrode being made of the double perovskite material according to any one of claims 1 to 4.
1. A reversible protonic ceramic electrochemical cell comprising:
10. The electrolyte material is BaZr 0.1 C 0.7 Y 0.1 Yb 0.1 O 3-δ where δ is the oxygen vacancy content; and / or The material of the anode support layer is NiO and BaZr 0.1 C 0.7 Y 0.1 Yb 0.1 O 3-δ Wherein NiO and BaZr 0.1 C 0.7 Y 0.1 Yb 0.1 O 3-δ and / or The reversible protonic ceramic electrochemical cell further includes a transition layer disposed between the anode support layer and the electrolyte, and preferably includes a transition layer made of NiO and BaZr. 0.1 C 0.7 Y 0.1 Yb 0.1 O 3-δ Wherein NiO and BaZr 0.1 C 0.7 Y 0.1 Yb 0.1 O 3-δ The mass ratio of 10. The reversible protonic ceramic electrochemical cell of claim 9.
Citation Information
Patent Citations
Medium and low temperature reversible proton ceramic electrochemical cell oxygen electrode material and preparation method and application thereof
CN114976065A
Production of perovskite-structure multiple oxide deposit
JP1996310802A
Novel cathode and electrolyte materials for solid oxide fuel cells / ion transport membranes
JP2009519191A
Precursor aqueous solution for metal composite oxide formation, manufacturing method of air electrode for solid oxide type fuel battery, and solid oxide type fuel battery unit cell
JP2022013200A